Manajemen Literasi Keagamaan di SMAN I Kota Kediri - Ahmad Masrukin; Siti Wahyuni (Indonesian Journal of Humanities and Social Sciences, 2022)
Literacy is a basic need in the world of education. Schools must organize a literacy movement program because the literacy rate for students is shallow. This impacts the success of improving character and knowledge development in Indonesia. In this context, this article describes the management of religious literacy at SMAN I Kediri City. This paper uses a qualitative research method with a case study approach. The key informants are the principal and the head of the Literacy Movement program. The results of this study indicate that the management of the literacy movement is built based on habituation efforts and making guidelines for the use of literacy programs, and making policies based on the curriculum for strengthening character education. Literacy management or management is very effective in learning at SMAN I Kota Kediri, especially in religious education.